2010
DOI: 10.1111/j.1365-2311.2009.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

A facultative mutualism between aphids and an invasive ant increases plant reproduction

Abstract: Abstract. 1. The consequences to plants of ant-aphid mutualisms, particularly those involving invasive ants, are poorly studied. Ant-aphid mutualisms may increase or decrease plant fitness depending on the relative cost of herbivory by ant-tended aphids versus the relative benefit of increased ant suppression of other (non-aphid) herbivores.2. We conducted field and greenhouse experiments in which we manipulated the presence and absence of cotton aphids (Aphis gossypii ) on cotton plants to test the hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 51 publications
3
53
0
2
Order By: Relevance
“…For example, it may have arisen because of differences in rates of herbivory in intact and invaded plots, if P. chinensis does not prey on the herbivores of H. arifolia to the same extent as native ant species do (Holway et al 2002;Styrsky and Eubanks 2010). However, the percentage of H. arifolia with apparent damage by herbivores did not differ between invaded (12% ± 3.60) and intact plots (7% ± 2.60) (t = 1.08, n = 23, P = 0.29).…”
Section: Resultsmentioning
confidence: 99%
“…For example, it may have arisen because of differences in rates of herbivory in intact and invaded plots, if P. chinensis does not prey on the herbivores of H. arifolia to the same extent as native ant species do (Holway et al 2002;Styrsky and Eubanks 2010). However, the percentage of H. arifolia with apparent damage by herbivores did not differ between invaded (12% ± 3.60) and intact plots (7% ± 2.60) (t = 1.08, n = 23, P = 0.29).…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of this Other study showed that Dermaptera of genus Dorus are efficient herbivorous predators in corn monoculture (see Cruz 1991). Additionally, Buschman et al (1977) Some studies have shown that the result of ant-plant interaction is dependent of the species of predatory ants involved interaction (Byk & Del-Claro, 2010;Calabuig et al, 2015) and of the strategies of herbivorous against predation (Bächtold & Alves-Silva, 2013;Carita et al, 2006;Styrsky & Eubanks, 2010). Nevertheless, little is known about the behavior between pairs (predator-prey) determining plant protection.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the ant T. erraticum not only improved the performance of A. gossypii colonies in terms of the population growth rates of all the different sized aphid colonies (El-Ziady & Kennedy, 1956;Flatt & Weisser, 2000;Powel & Silverman, 2010;Styrsky & Eubanks, 2010), but also benefi ted the aphid's host plant (Hansen et al, 2006). The positive consequences of the ant-aphid system for the host plant, in the absence of aphid natural enemies and alternative herbivores, probably indicates that ants (as the active partners in the mutualism) can affect the fi tness of the aphid's host plant as long as the requirements of the colony are satisfi ed.…”
Section: Source Of Variationmentioning
confidence: 99%
“…The cost to benefi t ratio in mutualism changes with the intrinsic features of both partners (e.g. the initial number of partners at the commencement of a relationship) and biotic/abiotic environmental factors (Stadler & Dixon, 1998;Styrsky & Eubanks, 2010;Yoo & Holway, 2011;Barton & Ives, 2014;Singh et al, 2016). Thus, mutualism has a context-dependent aspect, that is, the net benefi ts for a given species depend on ecological conditions (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%